Phase evolution of turbostratic boron nitride during the deposition of cubic boron nitride film - Kim, HS; Choi, IH; Baik, YJ (CAMBRIDGE UNIV PRESS, 2002)
The formation of turbostratic boron nitride (tBN) phase on the cubic boron nitride (cBN) phase was investigated at specific conditions. The cBN film was deposited oil the Si substrate by unbalanced magnetron sputtering. When the bias voltage at the substrate was adjusted to -85 V, the tBN phase nucleated on the cBN phase and grew simultaneously with the cBN phase. This was a critical bias voltage below which only the tBN phase was formed. The surface morphology of this film was typically shown as nodules dispersed on a very flat surface. The formation of nodulelike tBN phases seemed to be caused by a small variation of local stress on the growth surface. Once the nucleation of the nodulelike tBN phase occurred, the growth of tBN phase was accelerated. Transmission electron microscopy result showed evidence of the stress relaxation of the film caused by the formation of tBN phase at the interface of the tBN and cBN phases.
Keywords: STRESS-INDUCED FORMATION; THIN-FILMS; C-BN; ION IMPACT; GROWTH; MODEL